Onigocia sibogae, a replacement name for a distinct species of flathead fish, Platycephalus grandisquamis Weber, 1913 (Teleostei: Platycephalidae) - Imamura, Hisashi (Zootaxa, 2011)
A replacement name, Onigocia sibogae, is given for a platycephalid fish, Platycephalus grandisquamis Weber, 1913, being preoccupied by Platycephalus grandisquamis Regan, 1908. Although this species has been considered to be conspecific with Onigocia oligplepis (Regan, 1908), it was revealed that its five extant syntypes include three species and one of them is a distinct species from congeners of the genus, including O. oliglepis. To avoid taxonomic confusion, the lectotype (ZMA 112434, 51.2 mm SL) of O. sibogae is designated here. Onigocia sibogae differs from seven congeners in having usually I+VII-11 dorsal and 11 anal fin rays, eight caudal fin rays, 30–31 lateral line scales, anterior two or three scales with spine, three scales between second dorsal fin and lateral line, no ocular and interopercular flaps, upper iris lappet usually finely crenate, two or three antrorse lachrymal spines, usually no spines on the inner ridge of the lachrymal, 2–5 preocular spines, no notch on the suborbital ridge below the eye, suborbital ridge serrated by 16–26 small spines, and 2– 4 distinct blackish spots on middle and posterior portions of the pelvic fin rays.